The Development of Grade 10 Students' Mental Models on Solutions Through Model-Centered Instruction - Yuanphan, Yada; Nuangchalerm, Prasart (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2023)
This study aimed to construct the mental models of students in the 10th grade in order to attain a higher level of mental models by adopting a model-centered education sequence. This might be accomplished by adopting a model-centered instruction sequence. The research group consisted of 33 students who were all in the tenth grade at one school in the Mahasarakham province of Thailand during the second semester of the academic year 2021. The following instruments were utilized in the course of this research: 1) six different lesson plans, each with its own set of answers, that utilize a model-centered instructional technique, 2) mental model test, 3) students’ notebook, and 4) teacher’s note. Statistics such as the percentage, the mean, and standard deviation were applied in the process of doing the data analysis. The result revealed that the majority of students have accurate mental representations of scientific models, the adoption of a model-centered education sequence can help students gain more achievement. When it comes to accurately preparing diluted solutions, boiling points of solutions, and freezing points of solutions, the proportions of accurate mental models were 45.5, 51.5, and 48.4 respectively. It has been shown that the percentages of individuals who have entirely incorrect mental models, flawed mental models, incoherent mental models, and those who have no reaction are all on the decline.